2007
DOI: 10.1002/art.22304
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of human cartilage tissue to low concentrations of blood for a short period of time leads to prolonged cartilage damage: An in vitro study

Abstract: Objective. Joint bleeding, or hemarthrosis, leads in time to severe joint damage. This study was carried out to test the in vitro thresholds of exposure time and concentration that lead to irreversible joint damage, to add to the discussion on the usefulness of aspiration of the joint after a hemorrhage.Methods. Explants of healthy human articular cartilage tissue were cultured in the presence or absence of 50% (volume/volume) blood for 1, 2, 3, or 4 days or in the presence of 0%, 5%, 10%, 20%, 30%, or 50% (v/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 37 publications
6
112
2
4
Order By: Relevance
“…32 Furthermore, joint bleeding affects the synovial tissue, resulting in synovitis and subsequent articular cartilage damage, mainly caused by the excretion of tissue-destructive mediators, such as enzymes and cytokines. 14,15,[33][34][35] In conclusion, our results suggest that there are clinical differences between HB and HA and that the degree of arthropathy is more severe in HA patients, as supported by the higher number of hemarthrosis and lower levels of OPG both in serum and synovium. Our data suggest that the synovitis may play a crucial role in blood-induced arthropathy provoking an overreaction which subsequently becomes independent from bleeding, as postulated in other studies.…”
Section: Discussionsupporting
confidence: 62%
“…32 Furthermore, joint bleeding affects the synovial tissue, resulting in synovitis and subsequent articular cartilage damage, mainly caused by the excretion of tissue-destructive mediators, such as enzymes and cytokines. 14,15,[33][34][35] In conclusion, our results suggest that there are clinical differences between HB and HA and that the degree of arthropathy is more severe in HA patients, as supported by the higher number of hemarthrosis and lower levels of OPG both in serum and synovium. Our data suggest that the synovitis may play a crucial role in blood-induced arthropathy provoking an overreaction which subsequently becomes independent from bleeding, as postulated in other studies.…”
Section: Discussionsupporting
confidence: 62%
“…These synovial changes indirectly damage and destroy cartilage, but more recent data have shown that cartilage may be directly and independently affected by haemarthrosis. Biochemical markers of chondrocyte damage, such as impaired proteoglycan synthesis, may be seen after relatively short exposure to blood [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, physical factors such as joint loading may act synergistically to cause long-term joint damage after joint bleeds [7]. In vitro studies demonstrate that these changes occur in a doseand time-dependent manner, and that a duration of joint exposure to blood as short as 2 days may be sufficient to initiate long-term changes [5]. These issues may be important in guiding treatment for haemarthrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Hemophilia is characterized by frequent intra-articular and intramuscular bleeding episodes, causing damage to joint [1,2] and soft tissue, therefore, predisposing to arthropathy and musculoskeletal dysfunction [3,4]. Treatment of hemophilia with factor replacement aims to minimize structural damage to joints and maximize patients' functional independence and quality of life [5].…”
Section: Introductionmentioning
confidence: 99%